Tantangan dan Solusi Dalam Menangani Kasus Perceraian Internasional: Pespektif Hukum Perdata Internasional - Cahyo Danang Prayugo; Real Figo Pratama; Lintang Zufar Satyanagama; Muhammad Naufal Nabiila; Afiifah Shofiana Wafaa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research discusses the main forms of handling of divorce cases that occur internationally. The aim of this research is to identify and comprehensively analyze the main challenges in handling international divorce cases, seen from the perspective of international private law. The main challenge is identifying and overcoming legal obstacles that arise when the parties involved come from different jurisdictions. These factors include differences in private international law, legal norms, and complex legal procedures. In addition, cultural and language differences can complicate the process of handling divorce cases. Different jurisdictions and private international law procedures may also affect the rights and obligations of the parties involved. Therefore, a thorough understanding of these differences is essential to ensure fairness and effectiveness in the resolution of international divorce cases. By detailing these challenges, this research aims to contribute to further understanding of the complex legal issues in the handling of international divorce cases and unlock the potential for developing more coordinated and efficient legal frameworks in cross-border contexts.